Empowering Communities: A Narrative Inquiry on Educational Volunteers’ Role in Literacy Initiatives across Remote Indonesian Regions - Mia Febriana; Abdul Bari Khan (PAEDAGOGIA, 2025)
Education in remote areas, specifically concerning literacy, has emerged as a critical issue on the Indonesian government’s agenda, with an urgent need for effective intervention strategies to initiate and sustain literacy movements. Addressing the unique challenges of geographic isolation, limited resources, and local community engagement is pivotal. This study investigates these specific literacy challenges, focusing on remote regions by examining the experiences of three education volunteers in Seram Bagian Timur Regency, Maluku Barat Daya Regency, and Wakatobi Regency. This study employed a narrative inquiry approach to explore the literacy challenges and volunteer experiences in remote areas of Indonesia. Data were collected through in-depth interviews and analyzed using the constant comparative method to detail the complex interplay of volunteer background, motivations, encountered obstacles, and community-driven solutions that bolster literacy efforts. Our findings delineate four critical aspects: 1) the diverse backgrounds of the volunteers initiating literacy movements, 2) their intrinsic and extrinsic motivations, 3) the barriers they faced including logistical, cultural, and resource-based challenges, and 4) the significant role of community empowerment in overcoming these barriers and sustaining literacy initiatives. This research suggests that promoting literacy in Indonesia's remote areas can serve as a model for similar efforts elsewhere, ultimately contributing to regional educational development.